A generalized quantitative antibody homeostasis model: maintenance of global antibody equilibrium by effector functions. Issue 11 (17th November 2017) - Prechl, József
Abstract : The homeostasis of antibodies can be characterized as a balanced production, target‐binding and receptor‐mediated elimination regulated by an interaction network, which controls B‐cell development and selection. Recently, we proposed a quantitative model to describe how the concentration and affinity of interacting partners generates a network. Here we argue that this physical, quantitative approach can be extended for the interpretation of effector functions of antibodies. We define global antibody equilibrium as the zone of molar equivalence of free antibody, free antigen and immune complex concentrations and of dissociation constant of apparent affinity: [Ab]=[Ag]=[AbAg]= K D . This zone corresponds to the biologically relevant K D range of reversible interactions. We show that thermodynamic and kinetic properties of antibody–antigen interactions correlate with immunological functions. The formation of stable, long‐lived immune complexes correspond to a decrease of entropy and is a prerequisite for the generation of higher‐order complexes. As the energy of formation of complexes increases, we observe a gradual shift from silent clearance to inflammatory reactions. These rules can also be applied to complement activation‐related immune effector processes, linking the physicochemical principles of innate and adaptive humoral responses. Affinity of the receptors mediating effector functions shows a wide range of affinities, allowing the continuous sampling of antibody‐bound antigen over the complete range of concentrations. The generation of multivalent, multicomponent complexes triggers effector functions by crosslinking these receptors on effector cells with increasing enzymatic degradation potential. Thus, antibody homeostasis is a thermodynamic system with complex network properties, nested into the host organism by proper immunoregulatory and effector pathways. Maintenance of global antibody equilibrium is achieved by innate qualitative signals modulating a quantitative adaptive immune system, which regulates molecular integrity of the host by tuning the degradation and recycling of molecules from silent removal to inflammatory elimination. Adaptive immunity: A mathematical model of antibody equilibrium: A mathematical model describes how the immune system maintains equilibrium between free antibody and antigen, and antibody/antigen complexes. József Prechl of the Hungarian Academy of Sciences (MTA) in Budapest has developed a quantitative model, using mathematical formulas, to describe antibody functions. The model shows that the part of the immune system responsible for developing acquired immunity by means of antibodies, adaptive immunity, tends toward an equilibrium state where the concentrations of free antibody, free antigen, and bound antibody/antigen complexes are in balance with each other. This equilibrium ultimately determines the fate and lifetime of these molecules and creates an environment that allows the immune system to continuously recognize foreign invaders, target them through binding antibodies to their surface receptors, and then remove the antibody/antigen complexes in a process of 'self' maintenance and 'non‐self' expulsion.